2020
DOI: 10.2139/ssrn.3569883
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Viral Epidemic Outbreaks on Mental Health of Healthcare Workers: A Rapid Systematic Review and Meta-Analysis

Abstract: Background: This study aimed at examining the impact of providing healthcare during health emergencies caused by viral epidemic outbreaks on healthcare workers' (HCWs) mental health; to identify factors associated with worse impact, and; to assess the available evidence base regarding interventions to reduce such impact.Method: Rapid systematic review. We searched MEDLINE, Embase, and PsycINFO (inception to August 2020). We pooled data using random-effects meta-analyses to estimate the prevalence of specific m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
17

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 53 publications
1
3
0
17
Order By: Relevance
“…A rapid systematic review conducted on 61 studies revealed that pooled prevalence for anxiety was 45%, to 69%, followed by depression (38% to 60%); and acute stress disorder (31%, to 82%). 11 …”
Section: Introductionmentioning
confidence: 99%
“…A rapid systematic review conducted on 61 studies revealed that pooled prevalence for anxiety was 45%, to 69%, followed by depression (38% to 60%); and acute stress disorder (31%, to 82%). 11 …”
Section: Introductionmentioning
confidence: 99%
“…Healthcare workers had to face a new disease as well as its potential effects on their mental health, including burnout and symptoms of depression, anxiety, insomnia, grief and the development of post-traumatic stress disorder [ 1 , 2 ]. Deterioration in workers’ mental health may result from an increase in work-related stress caused by the need to change work procedures and to adapt to a changed work environment, as well as exposure to traumatic experiences [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Una revisión sistemática (23), una reflexión (24), un análisis crítico (25) y dos revisiones narrativas (26,27), identificaron factores que influyen en los niveles de estigmatización que presenta el personal de salud durante la pandemia de COVID-19. Un análisis crítico en Estados Unidos (25), describió el efecto de diversas pandemias (síndrome respiratorio agudo grave [SARS, por su sigla en inglés], ébola y enfermedad por el coronavirus 2019 (COVID-19, por su sigla en inglés) durante y después del brote infeccioso, y observó niveles altos de estigmatización hacia el personal de salud.…”
Section: Estigmatizaciónunclassified
“…Una revisión sistemática en España (23), identificó que el sentimiento de rechazo social y falta de apoyo familiar influyen en el trabajo clínico durante un brote infeccioso, con aumento de la estigmatización, mientras que una revisión narrativa en el mismo país indicó que el apoyo social tiene un papel protector (26). Una reflexión en Brasil (24) indicó que la discriminación tiene un efecto negativo en la conducta y la función social y familiar del personal de salud.…”
Section: Estigmatizaciónunclassified